The Impact of Internal Audit in the Case of PT. Xyz Bandung Regency on the Effectiveness of Internal Control - SUMADI, Alifiani Sunke; BAYUNITRI, Bunga Indah (PT Keberlanjutan Strategis Indonesia, 2024)
.To ensure that the company's internal control operates effectively to achieve organizational goals, an internal audit is essential. The number of layoffs, the prevalence of defective goods that cause a decrease in orders, and the misuse of checking accounts by directors for personal gain are just a few of the problems found based on data from PT. XYZ Bandung Regency in 2021 to 2024. This shows how important internal audit is in strengthening internal control of the business. The direction of the author's article is aimed at finding the success of XYZ's internal control in Bandung Regency as determined by the internal audit of PT. The methodology used in the author's article combines a descriptive approach with purposive sampling. The author's article group consists of sixty-three people from PT. 166 XYZ employees. The data were analyzed using a simple straight-line data analysis technique with a maximum control level of 5%, assisted by SPSS version 23. This article shows that the effectiveness of internal control is significantly influenced by internal audit. Internal audit increases the effectiveness of internal control by 71.9%. Therefore, effective internal audit practices can improve internal control and reduce the possibility of losses caused by weaknesses in the control system.